THE SCIENTIFICATION OF PSYCHOLOGY: THE PROBLEM OF CONSCIOUSNESS AND UNCONSCIOUSNESS - PETROSYAN, GAGIK (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
The problem concerning the subject of psychology in the period of the formation of scientific empirical psychology is examined in the article. The author attempts to show the roots of the psychology of consciousness; its philosophical, theoretical and methodological background. It is shown that both the phenomenological psychology of consciousness and the physiological psychology of consciousness are methodologically inconsistent and have no solid theoretical foundations. And the sole foundation for the psychology of consciousness, according to the author, is the psychology of the unconscious.